Robotic right‐sided colon cancer surgery: Dissecting the outermost layer of the autonomic nerve along the superior mesenteric artery - Dai Shida; Yuka Ahiko; Naoki Sakuyama; Satoko Monma; Shigehiro Kojima (Annals of Gastroenterological Surgery)
Abstract In right‐sided colon cancer surgery, lymph node dissection around the superior mesenteric artery is necessary but technically challenging. Here we introduce the concept of “outermost layer‐oriented robotic surgery” to improve the safety, efficacy, and reproducibility of superior mesenteric artery nodal dissection. In this procedure, the thin, loose connective tissue layer between the autonomic nerve sheath of the superior mesenteric artery and adipose tissue bearing lymph nodes, termed “the outermost layer of the autonomic nerve,” is dissected. The procedure exposes the outermost layer of the nerve plexus covering the surface of the superior mesenteric artery with a width of approximately 1 cm, enabling direct visualization of the anatomy of the main arteries and, if they exist, jejunal veins which cross the superior mesenteric artery ventrally. This allows for sufficient dissection of main lymph nodes at the roots of the ileocolic artery, right colic artery, and middle colic artery and minimizes the risk of unforeseen bleeding. Thirty‐nine patients underwent robotic right hemicolectomy with this procedure. No intraoperative complications were observed. The median number of dissected lymph nodes was 50, including 16 main lymph nodes. The median operative time was 284 min, blood loss was 50 mL, and the median postoperative hospital stay was 8 days. Postoperative complications included two cases of Clavien–Dindo classification grade II, with no cases of grade III or higher. Chylous leakage as well as intractable diarrhea were not observed in any case. These findings demonstrate that the procedure can achieve safe and reliable lymph node clearance.